STATE AND PROBLEMS OF LIVESTOCK DEVELOPMENT IN UKRAINE - DUKHNYTSKYI, Bogdan; DUKHNYTSKYI, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines dynamics of production the main groups of livestock products (meat, milk, eggs) in Ukraine from 2000 to the present. Currently, historically lowest indicators of total milk supply are observed. Special attention is paid to changes in the number of cattle, pigs and poultry for the analyzed period. The number of cattle, cows and pigs is also the smallest. The cost of production in livestock and crop cultivation is compared, with a significant advantage of the latter being noted. The participation of households in production of studied livestock products is considered. Their dominant role in milk production, providing half of the egg supply and auxiliary importance in meat segment are clarified. The key problems of Ukrainian livestock farming, characteristic of all its main areas, are identified. The negative factors that hinder development of meat and dairy cattle breeding, pig breeding and poultry farming are listed separately. Necessary state support is provided, which would contribute to the restoration and better resilience of the industries to modern challenges. Main provisions of the Concept of State Target Economic Program for Development of Livestock for the period until 2033 are characterized, which is designed to promote formation of effective industry in accordance with conditions of the European Union. An assessment of prospective measures and indicators of development livestock sector under the conditions of relative stability the socio-economic situation in our country is carried out. According to the forecasts of FAO and OECD, in 2033, compared to current volumes, meat production in Ukraine will practically not change, the amount of milk will continue to decrease slightly, but the supply of eggs should increase by 15%. Our country will continue to meet the needs of domestic food market with all types of livestock products, while remaining an active participant in the relevant world markets.